Comparison of Treatment Outcomes Between Intravenous Immunoglobulin and Steroid Therapy in Pediatric ITP (Idiopathic Thrombocytopenic Purpura): Intravenous Immunoglobulin and Steroid Therapy in Pediatric ITP - Ali, Zulfiqar; Zulqarnain, Arif; Adil, Muhammad Kamran; Fawad, Usman; Ahmad, Safwan; Hanif, Amir (Pakistan Journal of Health Sciences, 2026)
Idiopathic Thrombocytopenic Purpura (ITP) is a common and significant bleeding disorder in children with variable underlying etiologies. Objectives: To compare the short-term effectiveness and safety of IVIg versus corticosteroids in children with newly diagnosed ITP. Methods: An observational, cross-sectional comparison was conducted at a tertiary pediatric care center over a period of one year. Using consecutive sampling, 210 children were assigned to initial therapy with IVIg (n=105) or corticosteroids (n=105). Primary endpoints were time to platelet recovery and complete response by day 7; secondary endpoints included hospital stay, relapse ≤3 months, and adverse events. Group comparisons used Mann–Whitney U or chi-square/Fisher’s exact tests; multivariable logistic regression adjusted for age, gender, and baseline platelet count. Results: IVIg led to faster recovery (median 2 vs 4 days) and shorter hospital stay (3 vs 5 days), both p<0.001; higher complete response by day 7 (90.5% vs 71.4%, p<0.001); lower relapse (9.5% vs 21.0%, p=0.012) and fewer adverse events (11.4% vs 33.3%, p<0.001). IVIg independently predicted day-7 complete response (OR 4.5, 95% CI 1.9–10.8). Conclusions: In this non-randomized cohort, IVIg showed superior short-term effectiveness and safety versus corticosteroids.